2017
DOI: 10.3390/foods6090083
|View full text |Cite
|
Sign up to set email alerts
|

Glycemic Responses, Glycemic Index, and Glycemic Load Values of Some Street Foods Prepared from Plantain (Musa spp., AAB Genome) in Côte d’Ivoire

Abstract: The glycemic index (GI) and glycemic load (GL) of four culinary preferences including five local street dishes prepared from three varieties of plantain at different maturity stages was determined. The GI was obtained following ISO/FDI 26642:2010 protocol, and the GL was calculated from test foods’ GI, considering the amount of available carbohydrate in the traditional portion size. GI values were 44 for Klaclo (with Ameletiha variety at all black stage), 39 for Aloco (with Agnrin variety at full yellow stage)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
4
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 16 publications
1
4
0
Order By: Relevance
“…The presence of fat in the product delays stomach emptying, which, in turn, slows the absorption of carbohydrates [45]. Similar to this study, Kouamé et al [46] studied the GI and GL of some street foods prepared from plantain and showed a significant inverse relationship between GI and total carbohydrate content, while there was no correlation between GI and protein content in the studied foods [46]. Results of own studies and the above-cited discussions confirmed that food products made with the use of whole-grain raw materials or with the addition of mixtures with a high content of dietary fibre had a lower GI than dishes made of flour from purified grains.…”
Section: Discussionsupporting
confidence: 76%
“…The presence of fat in the product delays stomach emptying, which, in turn, slows the absorption of carbohydrates [45]. Similar to this study, Kouamé et al [46] studied the GI and GL of some street foods prepared from plantain and showed a significant inverse relationship between GI and total carbohydrate content, while there was no correlation between GI and protein content in the studied foods [46]. Results of own studies and the above-cited discussions confirmed that food products made with the use of whole-grain raw materials or with the addition of mixtures with a high content of dietary fibre had a lower GI than dishes made of flour from purified grains.…”
Section: Discussionsupporting
confidence: 76%
“…Some non-Nigerian authors found that three varieties of banana had moderate GI of between of 61-69% [26] . In contrast to the above, Kouamé, et al, [27] researched on Glycemic Responses, Glycemic Index, and Glycemic Load Values of Some Street Foods Prepared from Plantain (Musa spp., AAB Genome) in Côte d'Ivoire, and found low GI values for three varieties of Musa paradisiaca normalis. However, a high glycaemic index of 89 was reported for the fourth specie.…”
Section: Discussionmentioning
confidence: 99%
“…So it could increase the insulin response. And, more GL, the higher the food contains glycemic carbohydrate [14] [15]. Thus, Néré juice would be most aggressive to the body.…”
Section: Discussionmentioning
confidence: 99%